HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG MAKANAN PENDAMPING ASI DENGAN STATUS GIZI PADA ANAK BALITA DI PUSKESMAS TIKALA BARU MANADO - Nonce Nova Legi (Jurnal GIZIDO, 2014)
Knowledge of mother about baby child nutrition until five year very is determining of health ofand child of nutritionwell-balanced. With good knowledge all old fellow can keep in good healthand child of nutrition child can be well-balanced. Because Status of nutritionbaby until five yearrepresent one of the indicator which is depicting mount prosperity of society. Food of substitutionASI ( MP-ASI) represent other food which besides ASI. This Food can in the form of preparedfood peculiarly or modified family food. Target of this Research is Know Relation MountKnowledge Of Mother About Food of substitution ASI With Status of nutrition At Child Baby untilfive year.This Research type use analytic descriptive research desain with approach of CrossSectional. this Population Research is entire all mother owning child of Child Baby until five yearin Center health of society of TikalaBaru and this research is amount of population 2.678responder, with amount of sample 50 responder, instrument the used is Sheet Form and ofQuesioner. used by Analysis Date is bivariate and univariat with test of Chi-Square.Result of research there are relation which is signifikan between Knowledge Of Mother WithStatus of nutrition At Child Baby until five year (p=0.004). Pursuant to result of research, hencecan be concluded that knowledge of mother at most at category knowledge of goodness counted31 responder (62%) and status of gizi which residing in many at status of nutrition good counted35 responder ( 70%), hence from that officer of health in Center health of society of TikalaBarurequire to conduct counselling to motivate all mother old fellow to increase knowledge aboutpattern eat good utilize to increase status of nutrition good at baby child until five year, utilize toprevent disease to be suffered by baby child until five year